Early osteoarthritis after slipped capital femoral epiphysis: Cartilage degeneration, residual deformity and patient-reported outcome in 25 patients. (4th March 2018) - Helgesson, Lukas; Johansson, Peter Kälebo; Aurell, Ylva; Tiderius, Carl-Johan; Kärrholm, Johan; Riad, Jacques
Abstract : Background and purpose — Slipped capital femoral epiphysis (SCFE) results in a more or less pronounced deformity of the proximal femur, sometimes causing impingement and early osteoarthritis. We studied early osteoarthritis after SCFE and the association with deformity and self-reported hip function, pain, and quality of life. Patients and methods — 9 women and 16 men, mean age 32 (21–50) years, 19 with unilateral and 6 with bilateral SCFE, participated. All patients had primarily been operated by pin or screw with no attempt at reposition of the slip. Hips were examined by delayed gadolinium-enhanced magnetic resonance imaging of cartilage (dGEMRIC), which quantifies and locates cartilage degeneration. Plain radiographs were used to measure deformity as determined by the alpha angle. Outcome was assessed by Oxford hip score, Hip Groin Outcome score and EQ-5D-Visual scale. Results — In the 19 unilateral SCFE, on the slip side dGEMRIC mean value was 533 ms (SD 112, range 357–649) versus mean 589 ms (SD 125, range 320–788) on the non-slip side, (p = 0.01). The dGEMRIC correlated negatively to the alpha angle, correlation coefficient (CC) = –0.60, (p = 0.002). Oxford hip score, pain, and EQ-5D-Visual scale correlated to dGEMRIC CC =0.43 (p = 0.03), CC =0.40 (p = 0.05), and CC =0.49 (p = 0.01) respectively. Interpretation — After SCFE, even relatively mild residual hip deformity can be associated with cartilage degeneration. A high alpha angle was associated with worse cartilage status. The Oxford hip score identified symptoms even though our patients had not previously sought medical care after the index operation. Quality of life showed strong inverse correlation with cartilage degeneration. Objective assessment of early cartilage degeneration may be useful for treatment decisions and follow-up.